Policy Analysis Towards Karimunjawa Fisherman Catching Activity Regency Jepara - Bambang Argo Wibowo; Herry Boesono; Aryo Bayu Aditomo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
Karimunjawa National Park has pioneered in community development activities either through economic development, institutional strengthening, creation of alternative livelihoods and community capacity building since 1998. This activity was expected to raise the public's readiness to participate in maintaining and preserving the Karimunjawa National Park. However, the participation in this context could place people as an object, not as a subject. Therefore, further study is needed on whether the conservation of biological diversity embodied in the Karimunjawa National Parks zoning really gave positive impact on fishing communities and ecological sustainability. Moreover, fishermen only operate around coral reefs in shallow waters, making it very vulnerable to the violation of the National Park system zoning. The research method used in this research was descriptive method, while the sampling method used is purposive sampling. Data analysis methods used were SWOT and AHP analysis (Analytical Hierarchy Process). Policy strategies to overcome the issue of the National Parks zoning is increased security in Karimunjawa conservation areas, increased cooperation between the BTN, DKP, and Tourism Department to maintain the potential of coral reef fishery resources in order to remain sustainable, the allocation of funds from the government to assist BTN monitored overfishing, illegal fishing , and environmental pollution from damaged fishing gear, and the provision of an integrated socialization to encourage people to keep conserving the resources. Key words: Karimunjawa National Park zoning, biodiversity conservation, AHP (Analytical Hierarchy Process)